PERBEDAAN JUMLAH KROMOSOM IKAN GABUS (Channa Striata) DARI RAWA DATARAN RENDAH, DATARAN TINGGI DAN PASANG SURUT - Wahyu Angga Saputra; Muslim .; Ade Dwi Sasanti (Jurnal Akuakultur Rawa Indonesia, 2014)
ABSTRACT The aim of this research is to determine the chromosomes number of snakehead fish (Channa striata) from floodplain area, highland swamp, and tidal land. The research has done on December 2013 until January 2014 at Laboratorium Pengembangbiakan dan Genetika Ikan, Department of Aquaculture, Faculty of Fishries and Marine Science, Bogor Agricultural Institute, Laboratorium Dasar Perikanan dan Laboratorium Budidaya Perairan, Study Program of Aquaculture, Agriculture Faculty, Sriwijaya  University and Laboratorium Fisiologis Hewan, Mathematics and Natural Science Faculty, Sriwijaya University, Indralaya. The research was conducted by means of direct observation and analyzed descriptive through making preparations chromosome squash methods. The results showed no difference in diploid (2n) chromosome number of snakehead fish floodplain area as much ranges 40-42, highland swamps ranges 36-40 and tidal land ranges 38-40 and it can be concluded that the chromosomes amount of snakehead fish           between 36-42.   Keywords : Channa striata, Chromosome, Floodplain area, Highland swamp, Tidal Land